Uprising: An examination of sit-stand workstations, mental health and work ability in sedentary office workers, in Western Australia - Tobin, Rochelle; Leavy, Justine; Jancey, Jonine (IOS Press, 2016)
BACKGROUND: Office-based staff spend around three quarters of their work day sitting. People who sit for long periods while at work are at greater risk of adverse health outcomes. OBJECTIVE: The pilot study aimed to determine the effect of sit-stand workstations on office-based staff sedentary and physical activity behaviors, work ability and self-reported physical and mental health outcomes. METHODS: A two-group pre-post study design assessed changes in sedentary and physical activity behaviors (time spent sitting, standing and stepping and sit-stand transitions and number of steps taken) work ability and physical and mental health. Physical activity behaviors were measured using activPAL activity monitors and self-reported data on work ability and physical and mental health were collected using an online questionnaire. RESULTS: Relative to the controls (n=19), the intervention group (n=18) significantly decreased time spent sitting by 100 minutes (p<0.001) and increased standing time by 99 minutes (p<0.001). There was a decrease in self-reported current work ability when compared to lifetime best (p=0.008). There were no significant differences for all other sedentary behavior, other workability outcomes, physical health or mental health outcomes at follow-up. CONCLUSIONS: The Uprising Study found that sit-stand workstations are an effective strategy to reduce occupational sitting time in office-based workers over a one month period.